Career Motivation as a Mediator Between Financial Reward Perception, Job Market Stability and Accounting Career - Marvel Timotius Purnama; Imelda Suardi (Journal of Social Research, 2026)
Indonesia faces a critical paradox in the accounting profession: despite producing thousands of accounting graduates annually, the country has only one Certified Public Accountant (CPA) for every 186,000 citizens, which remains far below regional benchmarks. This study investigated the psychological mechanisms through which external career perceptions are transformed into genuine long-term career commitment among accounting students. Specifically, it examined the influence of financial reward perception and job market stability on the intention to choose accounting as a long-term career, with career motivation as a mediating variable. Grounded in Social Cognitive Career Theory and London’s Career Motivation Framework, this study proposed that external career perceptions do not directly translate into career commitment but must first be internalized through motivational states before generating sustained behavioral intentions. Data were collected from 150 undergraduate and graduate accounting students across three Indonesian universities. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed using SmartPLS 4. The results supported all seven hypotheses. Financial reward perception significantly predicted both career motivation and career intention. Job market stability emerged as the strongest predictor of career motivation and also significantly influenced career intention. Career motivation partially mediated the relationships between financial reward perception, job market stability, and career intention. These findings provide theoretical and practical implications for accounting education institutions and professional organizations seeking to address Indonesia’s shortage of Certified Public Accountant (CPA) talent.